When the beacon goes dark: Legitimacy repair work by subsequent actors in an emerging market category - Smith, Brett R.; Bergman, Brian J.; Kreiner, Glen E. (Journal of Business Venturing, 2021)
Extant research explains how entrepreneurial ventures can serve as a beacon in emerging market categories, blazing a trail for other ventures and contributing to their successful legitimation. However, what happens when a beacon is unsuccessful? Using a qualitative case study of particularly sensitive interviews and secondary data from the social venture accelerator category, we examine how subsequent entrants overcome recursive legitimacy challenges caused by beacon underperformance and failure. Through our study, we develop a model of legitimacy repair work, which consists of decoupling legitimacy assessments, prioritizing distinctiveness identity claims, and enabling selective generalization. Following legitimacy loss, we highlight how actors prioritize and sequence distinctiveness claims over legitimacy claims, which we refer to as distinctive legitimacy. We also identify a key mechanism of selective generalization, where identity claims are made to direct audience attention toward some (and not other) attributes of the organization and category to acquire resources. Our findings have important implications for new venture legitimacy: mitigating legitimacy loss, the process of optimal distinctiveness, and legitimacy management over time.